THE CORRELATION INTENSITY OF SOCIAL MEDIA USAGE WITH SLEEP QUALITY IN CLASS X STUDENTS IN SMK MUHAMMADIYAH 1 YOGYAKARTA: HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KUALITAS TIDUR PADA SISWA KELAS X DI SMK MUHAMMADIYAH 1 YOGYAKARTA - Suib Suib (Yayasan Pendidikan Medika Indonesia, 2020)
ABSTRACT Background: The development of technology and information has impact on adolescents, especially social media usage. Many adolescents are active in various social media to establish communication and familiarity with people around them. Social media usage can also cause dependence that has bad impact such as sleep needs are less fulfilled, causing decrease sleep quality. This research aimed to determine the correlation between intensity of social media usage with sleep quality in class X students in SMK Muhammadiyah 1 Yogyakarta. Method: This research design was descriptive correlational with cross sectional approach. This research population were 242 students of class X in SMK Muhammadiyah 1 Yogyakarta. The sample of this research were 71 respondents by used purposive sampling technique. Measuring instrument used questionnaire and data analysis used chi-square test. Results: This research showed that majority of respondents had high intensity of social media usage were 22 students (31,0%) and poor sleep quality were 47 students (66,2%). The results of chi-square test obtained x2 count of 17,800 > x2 tables of 7,815 and p value of 0,000 < 0,05 and correlation coefficient of 0,448. Conclusion: There was significant correlation between intensity of social media usage with sleep quality in class X students in SMK Muhammadiyah 1 Yogyakarta. Keywords: Social Media, Sleep Quality, Student